Liver X Receptor (LXR) partial agonists: Biaryl pyrazoles and imidazoles displaying a preference for LXRβ. Issue 2 (15th January 2015) - Kick, Ellen; Martin, Richard; Xie, Yinong; Flatt, Brenton; Schweiger, Edwin; Wang, Tie-Lin; Busch, Brett; Nyman, Michael; Gu, Xiao-Hui; Yan, Grace; Wagner, Brandee; Nanao, Max; et al.
Graphical abstract: Abstract: A series of biaryl pyrazole and imidazole Liver X Receptor (LXR) partial agonists has been synthesized displaying LXRβ selectivity. The LXRβ selective partial agonist18 was identified with potent induction of ATP binding transporters ABCA1 and ABCG1 in human whole blood (EC50 = 1.2 μM, 55% efficacy). In mice18 displayed peripheral induction of ABCA1 at 3 and 10 mpk doses with no significant elevation of plasma or hepatic triglycerides at these doses, showing an improved profile compared to a full pan-agonist.